(untitled) (Journal of Architectural Design, 2023)
This article highlights that the research carried out in the Barak Khan madrasah in Tashkent in the 16th century, archeological and engineering-geological research, conservation and repair work carried out in a timely manner by well-known experts in the field of protection of the monument indicates that the correct methods have been selected when creating the zones and restoration. And also, considered on the architectural aspects, the history of the phased restorations in different periods, styles and the current state of the Barak Khan Madrasah in Tashkent, the fact that its construction was formed in several stages.